2001
DOI: 10.1016/s0886-3350(01)01036-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cataract surgery on intraocular pressure control in glaucoma patients

Abstract: Cataract surgery substantially reduced IOP and the number of medications required for IOP control in glaucomatous eyes. Specifically, cataract extraction normalized the IOP in most eyes with ACG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
171
0
12

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(200 citation statements)
references
References 38 publications
17
171
0
12
Order By: Relevance
“…Many previous studies including ours 22 showed that CS lowers the IOP for several years; [23][24][25] this is consistent with the results obtained in this study. However, IOP in no eyes that underwent surgery was low enough to cause hypotension maculopathy, and was thus considered to be unrelated to the progression of ERM.…”
Section: Discussionsupporting
confidence: 93%
“…Many previous studies including ours 22 showed that CS lowers the IOP for several years; [23][24][25] this is consistent with the results obtained in this study. However, IOP in no eyes that underwent surgery was low enough to cause hypotension maculopathy, and was thus considered to be unrelated to the progression of ERM.…”
Section: Discussionsupporting
confidence: 93%
“…One part of the evidence of lens factor is that cataract extraction lowers IOP by improving the angle configurations in ACG. [15][16][17][18][19] In our study, TCPD was slightly increased after LI or PT. CPI was decreased after both procedures.…”
Section: Discussionsupporting
confidence: 47%
“…The drop in IOP observed after 1 month following cataract surgery was in agreement with previous investigations in which IOP has been reported to decrease post-operatively in the mid-to long-term. [1][2][3][4] A post-operative reduction in systemic blood pressure also occurred, however, patients are generally anxious on the day of their operation and more relaxed postoperatively that may have accounted for the observed change. The reduction in IOP and parallel reduction in systemic blood pressure in the cataract group postoperatively meant that OPP remained stable between visits.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] This outcome, which has been attributed to a widening of the anterior chamber angle, [5][6][7][8] has positive implications for glaucomatous eyes resulting in a reduced requirement for IOP-lowering medication in at least one study. 4 Hopkins 9 carried out a pilot study investigating ocular haemodynamics in a small group of cataractous eyes and reported a 20-30% decrease in pulsatile ocular blood flow (POBF) compared to normal healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation